A new and ecological method to quantify vancomycin in pharmaceutical product by infrared spectrometry - do Nascimento, Patrícia Aleixa [UNESP]; Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Slovenian Chemical Society, 2021)
Vancomycin, an antimicrobial, does not present quantitative method by infrared spectrometry in the literature for the evaluation of a pharmaceutical product. This technique is considered a clean alternative because in the main, there is no solvent involved and the generation of waste is reduced. So, the aim of this study was to develop and validate a new, ecological, low cost and fast method by infrared spectrometry using KBr and band between 1450-1375 cm-1. It was linear in the range of 1.0-2.0 mg/150 mg, with a correlation coefficient of 0.9994. Selective when the spectra of vancomycin reference and sample were compared. Precise by repeatability (2.29%) and intermediate precision (3.12%). Accurate with average recovery of 99.37% and robust when strength and compression time of the pellets and KBr brand were varied. Considering all the methods found in literature, there is not one using infrared spectrometry for quantitative purpose, so the method developed and validated could be considered an innovation and clean alternative. This is due to the fact that it is fast, easy to handle, low cost, and non-toxic as well as generating minimal waste. The method can be applied in the routine analysis of vancomycin dosage form and is an important option for the current and sustainable pharmaceutical analysis.
Keywords: Green analytical chemistry; Infrared spectrometric method; Pharmaceutical analysis; Sustainable alternative; Vancomycin